Phytochemical Analysis of the Feed of the Tapanuli Orangutan as a Continuing Conservation Effort - Apriani Sijabat; Herna Febrianty Sianipar (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aims to determine the type of feed for the Tapanuli orangutan (Pongotapanuiliensis), and the phytochemical compounds contained in the diet of the Tapanuli orangutan (Pongotapanuiliensis). This research was conducted in the Batang Toru forest of South Tapanuli for sampling. This study used a line transect method with 4 transects I, II, III, IV) used to observe the diet of the Tapanuli orangutan, and the Physics Laboratory of the HKBP Nommensen Pematangsiantar University for phytochemical analysis. The results of this study obtained 11 types of nests HayunDolok (Syzygiumsp), Medang (Litseabrachystachys), Mayang (Palaquiumgutta), Laccatbodat (Shoreahopeifolia) and Hoteng (Quercusgemelliflora). Phytochemical compounds contained in orangutan feed are alkaloids, flavonoids, tannins and saponins.